Amazon Web Services (AWS) Linux operations - Jones, Richard A.; Safari eBooks ([Place of publication not identified] : Pearson, 2018)
"Amazon Web Services for Operations (AWS) Linux Operations LiveLessons is a video product designed to provide a guide to creating resources, organizing environments, and ongoing maintenance. The course covers methods and tools necessary to organize and automate numerous resources within the rich ecosystem of Amazon Web Services. Amazon Web Services for Operations (AWS) Linux Operations LiveLessons contains 9 focused lessons with more than 11 hours of video lecture, screencast, interactive monitor work, and live hands-on labs. Demonstrations of Amazon Web Services and third-party cloud solutions are included to provide a clear guide to performing common operational tasks and achieving a reliable, cost-effective, and automated environment."--Resource description page.
Presenter, Richard Jones.
Title from title screen (viewed September 27, 2017).
Keywords: Amazon Web Services (Firm); Linux; Web services; Cloud computing; Computer network architectures; Electronic books